Piezoelectric guided wave propagation - Laprus, W.; Danicki, E. (Archives of Acoustics, 2004)
A perfectly conducting strip embedded in a piezoelectric medium is considered. Waves propagating along the strip are investigated with the use of a surface impedance function which is suggested by the known surface impedance function for a perfectly conducting plane embedded in the medium. A dispersion equation for the waves is found and solved in the case of a narrow strip.